A new method for making treatment decisions for incapacitated patients: what do patients think about the use of a patient preference predictor?. Issue 4 (29th January 2016) - Wendler, David; Wesley, Bob; Pavlick, Mark; Rid, Annette
Abstract : Background: Surrogates frequently are unable to predict which treatment their charges would want and also can experience significant distress as a result of making treatment decisions. A new method, the patient preference predictor (PPP), has been proposed as a possible way to supplement the process of shared decision-making to address these two concerns. The PPP predicts which treatment the patient would want based on which treatment similar patients want in similar circumstances. The present article describes the results of the first evaluation to assess whether patients support the use of a PPP. Methods: Self-administered survey of patients at a tertiary care centre. Results: Overall, 1169 respondents completed the survey (response rate=59.8%). In the event that the respondent became unable to make decisions due to a car accident, 78.9% would want the PPP to be incorporated into the process of making treatment decisions for them. In contrast, 15.2% of respondents would not want the PPP to be used for them. Respondents who endorsed the PPP cited the possibility that its use could increase the chances that they receive the treatments they prefer and/or reduce the burdens on their surrogate decision-maker. Conclusions: The majority of respondents endorsed the possibility of incorporating a PPP into the process of shared decision-making based on its potential to increase surrogates' predictive accuracy and/or reduce surrogate distress. These data provide strong patient support for further research to assess whether, in practice, the use of a PPP can increase the chances that incapacitated patients receive the treatments they prefer and reduce the burden of making decisions on their surrogates.